Epithelial barrier dysfunction and associated diseases in companion animals: Differences and similarities between humans and animals and research needs - Ardicli, Sena; Ardicli, Ozge; Yazici, Duygu; Pat, Yagiz; Babayev, Huseyn; Xiong, Peng; Zeyneloglu, Can; Garcia-Sanchez, Asuncion; Shi, Li-Li; Viscardi, Oliva Giannelli; Skolnick, Stephen; Ogulur, Ismail; et al. (Allergy, 2024)
Since the 1960s, more than 350,000 new chemicals have been introduced into the lives of humans and domestic animals. Many of them have become part of modern life and some are affecting nature as pollutants. Yet, our comprehension of their potential health risks for both humans and animals remains partial. The "epithelial barrier theory" suggests that genetic predisposition and exposure to diverse factors damaging the epithelial barriers contribute to the emergence of allergic and autoimmune conditions. Impaired epithelial barriers, microbial dysbiosis, and tissue inflammation have been observed in a high number of mucosal inflammatory, autoimmune and neuropsychiatric diseases, many of which showed increased prevalence in the last decades. Pets, especially cats and dogs, share living spaces with humans and are exposed to household cleaners, personal care products, air pollutants, and microplastics. The utilisation of cosmetic products and food additives for pets is on the rise, unfortunately, accompanied by less rigorous safety regulations than those governing human products. In this review, we explore the implications of disruptions in epithelial barriers on the well-being of companion animals, drawing comparisons with humans, and endeavour to elucidate the spectrum of diseases that afflict them. In addition, future research areas with the interconnectedness of human, animal, and environmental well-being are highlighted in line with the "One Health" concept.
Keywords: Pets; Dogs; domácí zvířata; Cats; zvířata; Humans; Epithelium; Environmental Exposure; vystavení vlivu životního prostředí; psi; epitel; lidé; kočky; Animals